Road safety management - The need for a systematic approach - András Várhelyi (19772985) (2015)
To achieve significant improvements, there is a need for a systematic approach in Road Safety Management. The first step of such approach is to define the burden of road casualties in the country. Part of defining the burden is the monetary valuation of the prevention of a fatality accident. Such “values of statistical life” are derived in a number of countries, however, there is a large variation among these. Interestingly, a negative correlation seems to exist between the monetary valuation of a statistical life and the road safety situation of a country, namely, countries with low “values of statistical life” have poor road safety situation and vice versa. The next step is to get commitment from decision makers. There is an accumulated knowledge among road safety scientist on what strategies and measures are the most efficient, but without commitment from decision makers, these will not will not be realized. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.112